Actividades ludicas y su incidencia para fortalecer el proceso de aprendizaje en las área de matemáticas para los estudiantes - Tapia Pincay, Marcela Mariuxi (2019)
The present work has the objective of using the Ludic Activities and their Incidence to Strengthen the Learning Process in the Mathematics Area for students. Its main objectives are to analyze the recreational activities that make up a benchmark to acquire knowledge, which is why the need arises to know them and apply them within the educational environment of children in the area of mathematics, the proposal is based on the design of basic elements for the development of a strategy aimed at promoting development and teaching methods in children. In this way, recreational activities serve as resources that facilitate knowledge, skills, and skills in children with diverse abilities. In the background we find the subject of study with sufficient bibliography. On the theoretical basis we support the hypothesis. The particularity of this research is Field and bibliographic. The techniques that are the survey, interview, the questionnaire will be used. Through the analysis and interpretation of the results obtained that will allow establishing the visibility of the hypothesis that is based on the proposal to achieve a solution to the problem investigated, this work will be concluded with the analysis through the conclusions and recommendations of the most important points found in benefit of this work done